Decentralized Solutions for Developing Economies Addressing Energy Poverty Through Innovation - Groh, Sebastian; van der Straeten, Jonas; Edlefsen Lasch, Brian; Gershenson, Dimitry; Leal Filho, Walter; Kammen, Daniel M. (Springer Proceedings in Energy, 2015)
XXIV, 294 p. 84 illus., 25 illus. in color.